Effect of creatine supplementation on metabolism and performance in humans during intermittent sprint cycling - Finn, J. P.; Ebert, T. R.; Withers, R. T.; Carey, M. F.; Mackay, M.; Phillips, J. W.; Febbraio, M. A. (European Journal of Applied Physiology, 2001)
This double blind study investigated the effect of oral creatine supplementation (CrS) on 4 × 20 s of maximal sprinting on an air-braked cycle ergometer. Each sprint was separated by 20 s of recovery. A group of 16 triathletes [mean age 26.6 (SD 5.1) years. mean body mass 77.0 (SD 5.8) kg, mean body fat 12.9 (SD 4.6)%, maximal oxygen uptake 4.86 (SD 0.7) l · min-1] performed an initial 4 × 20 s trial after a muscle biopsy sample had been taken at rest. The subjects were then matched on their total intramuscular creatine content (TCr) before being randomly assigned to groups to take by mouth either a creatine supplement (CRE) or a placebo (CON) before a second 4 × 20 s trial. A muscle biopsy sample was also taken immediately before this second trial. The CrS of 100 g comprised 4 × 5 g for 5 days. The initial mean TCr were 112.5 (SD 8.7) and 112.5 (SD 10.7) mmol · kg-1 dry mass for CRE and CON, respectively. After creatine loading and placebo ingestion respectively, CRE [128.7 (SD 11.8) mmol · kg-1 dry mass] had a greater (P=0.01) TCr than CON [112.0 (SD 10.0) mmol · kg-1 dry mass]. While the increase in free creatine for CRE was statistically significant (P=0.034), this was not so for the changes in phosphocreatine content [trial 1: 75.7 (SD 6.9), trial 2: 84.7 (SD 11.0) mmol · kg-1 dry mass, P=0.091]. There were no significant differences between CRE and CON for citrate synthase activity (P=0.163). There was a tendency towards improved performance in terms of 1 s peak power (in watts P=0.07; in watts per kilogram P=0.05), 5 s peak power (in watts P=0.08) and fatigue index (P=0.08) after CrS for sprint 1 of the second trial. However, there was no improvement for mean power (in watts P=0.15; in watts per kilogram P=0.1) in sprint 1 or for any performance values in subsequent sprints. Our results suggest that, while CrS elevates the intramuscular stores of free creatine, this does not have an ergogenic effect on 4 × 20 s all-out cycle sprints with intervening 20-s rest periods.